2015
DOI: 10.1186/s12936-015-0882-1
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of diagnostic assays in Plasmodium falciparum malaria

Abstract: Background: Rapid diagnostic tests (RDT) and real-time PCR (qPCR) assays are sensitive for diagnosing malaria, but because they detect antigen and DNA, respectively, positivity may not reflect active infection. Performance characteristics of RDT and qPCR in Plasmodium falciparum positive specimens were evaluated over time to elucidate duration of positivity following conversion to microscopy negative. Methods:Specimens from patients with at least one specimen that was positive for P. falciparum by microscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
2
10
1
1
Order By: Relevance
“…In line with our findings, other studies on travelers have reported similar persistence of PCR positivity after curative treatment ( Dakic et al, 2014 , Phuong et al, 2015 ). A duration of positive microscopy and real-time qPCR up to five and 28 days, respectively, was observed in Serbia ( Dakic et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with our findings, other studies on travelers have reported similar persistence of PCR positivity after curative treatment ( Dakic et al, 2014 , Phuong et al, 2015 ). A duration of positive microscopy and real-time qPCR up to five and 28 days, respectively, was observed in Serbia ( Dakic et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…A duration of positive microscopy and real-time qPCR up to five and 28 days, respectively, was observed in Serbia ( Dakic et al, 2014 ). In addition, a study from Canada reports real-time PCR positivity up to 19 days after microscopy turned negative in successfully treated patients, and suggested the slow clearance of parasite DNA from the bloodstream, pointing out the risk of false positive PCR after treatment ( Phuong et al, 2015 ). Moreover, PCR positivity up to 42 days post-treatment has been observed in endemic areas where neither recrudescence nor reinfection were considered as underlying cause for positive PCR, with no further explanation or investigations into the actual cause of the long PCR positivity ( Aydin-Schmidt et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A duration of positive microscopy and real-time qPCR up to five and 28 days, respectively, was observed in Serbia (Dakic et al, 2014). In addition, a study from Canada reports realtime PCR positivity up to 19 days after microscopy turned negative in successfully treated patients, and suggested the slow clearance of parasite DNA from the bloodstream, pointing out the risk of false positive PCR after treatment (Phuong et al, 2015). Moreover, PCR positivity up to 42 days post-treatment has been observed in endemic areas where neither recrudescence nor reinfection were considered as underlying cause for positive PCR, with no further explanation or investigations into the actual cause of the long PCR positivity (Aydin-Schmidt et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…RDTs have been developed to detect antigens derived from malaria parasites; such tests often use a dipstick or cassette format, and provide results in 2–15 min offering a useful alternative to microscopy in situations where reliable microscopic diagnosis is not immediately available [ 10 ]. These assays identify parasite antigens such as HRP2, pLDH and pAldolase [ 2 , 11 ] and are routinely implemented due to their simplicity and rapid turnaround time, enabling them to work as a point-of-care diagnostic.…”
Section: Introductionmentioning
confidence: 99%
“…Currently available devices have also some limitations: batch-to-batch quality variation, species and density determination, persistent positivity, accuracy, and costs [ 12 ]; moreover, false negative results in the presence of high parasitaemia are reported [ 12 ]. The specificity of RDTs can be low, particularly in the setting of persistent antigenaemia post-treatment of P. falciparum infection, as well as non- falciparum species [ 10 ], although newer generation RDTs perform well in diagnosing P. vivax infections [ 15 ]. For all these reasons RDTs may be used in addition to, but not as a replacement for microscopy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%